2014
DOI: 10.1016/j.surfcoat.2014.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Observation and modeling of α-NiPtAl and Kirkendall void formations during interdiffusion of a Pt coating with a γ-(Ni-13Al) alloy at high temperature

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…2 exhibit X-ray diffraction patterns and backscattered electron (BSE) images of cross-sections of the Ni-12Al-10Cr/ electroplated-Pt system annealed 1 min, 15 min and 60 min at 1100°C under argon. Similar phases than the ones of the Ni-Al-Pt ternary system [5] were observed whatever the duration of the heat treatment was.…”
Section: Materials and Experimentssupporting
confidence: 67%
See 3 more Smart Citations
“…2 exhibit X-ray diffraction patterns and backscattered electron (BSE) images of cross-sections of the Ni-12Al-10Cr/ electroplated-Pt system annealed 1 min, 15 min and 60 min at 1100°C under argon. Similar phases than the ones of the Ni-Al-Pt ternary system [5] were observed whatever the duration of the heat treatment was.…”
Section: Materials and Experimentssupporting
confidence: 67%
“…The lattice parameter "a" of the two phases was similar (0.3878 nm and 0.3865 nm for α 1 and α 2 respectively) whereas their lattice parameter "c" differed (0.3586 nm and 0.3635 nm for α 1 and α 2 respectively). As reported in the Ni-Al-Pt system, α-NiPtAl formation was caused by the rapid diffusion toward the surface of Ni and Al [5,28], the uphill Al diffusion being favoured by the decrease in Al activity due to Pt [3].…”
Section: Chromium Effectmentioning
confidence: 67%
See 2 more Smart Citations
“…Second, the diffusion of Ni from the substrate to the outer layer is weak and the replenishment of Ni is not sufficient. Audigié et al suggested that the void location corresponds to the Al depletion zone (or the Pt diffusion front) [29]. However, no voids were observed in the two-phase coating.…”
Section: Discussionmentioning
confidence: 99%